Influência da morfologia no comportamento magnético em aglomerado de CoTPP - Rocha, Alberto José Moreira (Universidade Federal de São Carlos, 2022)
The study of magnetic properties in organic molecules with transition metals has been intense in recent decades, mainly due to the ease of changing their magnetic behavior, either through the introduction of different types of atoms or through changes due to proximity effects with other materials. This thesis we presents the investigation of the magnetic behavior of samples of Cobalt 5-10-15-20-meso-tetraphenylporphyrin (CoTPP) deposited on SiO2 surface. The results showed high values of magnetic moment which as a consequence, led to the appearance of superparamagnetism in samples with a morphological aspect a few deposit, which suggest an interdependence between the morphology and the magnetic response. With aid of morphological techniques, it was possible to suggest the causes magnetic response. These results indicate the possibility of altering the magnetic behavior from changes in the morphology of the samples.
Influence of morphology on magnetic behavior in CoTPP cluster
Keywords: Caracterização magnética; Caracterização morfológica; Superparamagnetismo; CoTPP; Magnetic characterization; Morphologic characterization; Superparamagnetism; CIENCIAS EXATAS E DA TERRA::FISICA